2017
DOI: 10.15171/ehem.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

Predicting arsenic and heavy metals contamination in groundwater resources of Ghahavand plain based on an artificial neural network optimized by imperialist competitive algorithm

Abstract: Background: The effects of trace elements on human health and the environment gives importance to the analysis of heavy metals contamination in environmental samples and, more particularly, human food sources. Therefore, the current study aimed to predict arsenic and heavy metals (Cu, Pb, and Zn) contamination in the groundwater resources of Ghahavand Plain based on an artificial neural network (ANN) optimized by imperialist competitive algorithm (ICA). Methods: This study presents a new method for predicting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…These methods provide a valid tool for estimating heavy metal contents in soil near mining and suburban regions, thus facilitating the management and assignment of human settlements and other natural resources. Previous studies have reported that statistical methods and artificial neural networks can be successfully applied for estimating various other heavy metal contents in soils in various regions [34][35][36][37]. In this study, four popular and dominant soft computing techniques were used for the estimation of heavy metals in soil.…”
Section: Discussionmentioning
confidence: 99%
“…These methods provide a valid tool for estimating heavy metal contents in soil near mining and suburban regions, thus facilitating the management and assignment of human settlements and other natural resources. Previous studies have reported that statistical methods and artificial neural networks can be successfully applied for estimating various other heavy metal contents in soils in various regions [34][35][36][37]. In this study, four popular and dominant soft computing techniques were used for the estimation of heavy metals in soil.…”
Section: Discussionmentioning
confidence: 99%
“…An MLP network is composed of one or more input layers, one or more of hidden layers and an output layer [23]. Recently, ANNs have been widely and successfully used [22][23][24].…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…An MLP network constitutes an input layer, one or such hidden layers, and an output layer (12). In recent years, ANNs are successfully used in environmental settings (13,31). In the current study, the Bayesian regularization algorithm was used to train ANN.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…In this regard, only 2.8% of water on earth is fresh water; therefore, groundwater resources are highly valued due to their certain properties such as wide-spread occurrence and availability, and also good quality as an ideal supply of drinking water; due to these reasons more than half of the world's population depend on groundwater for survival (1)(2)(3)(4)(5)(6)(7). During the last few decades, contamination of groundwater resources is among the most important environmental issues due to hazardous chemical compounds such as heavy metals, pesticides, and petroleum hydrocarbons (8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation